A COMPOSITION PATCH ANTENNA - S. A. Pogarsky; D. V. Mayboroda; S. M. Mykhaliuk (Radio Physics and Radio Astronomy)
Subject and Purpose. The paper presents results of numerical simulation of a composition patch antenna with a complex form factor. The design combines two structures, specifically, a disc and an annular resonator. The annular resonator is fed via a coplanar structure that involves cut-ins of different geometries. The feed connections are effectuated pointwise, such as to provide for galvanic contact between the central conductor of the coplanar line and the annular resonator, owing to the distributed electromagnetic coupling of the annular resonator and the aperture of the coplanar line’s outer conductor. The work has been aimed at finding an optimized set of antenna parameters.